I'm bored - Black, Michael Ian, 1971-; Ohi, Debbie Ridpath, 1962- (New York : Simon & Schuster Books for Young Readers, 2012)
When a bored girl meets a potato who finds children tedius, she tries to prove him wrong by demonstrating all of the things they can do, from turning cartwheels to using their imaginations.
"A Junior Library Guild selection"--Jkt. flap.
Ages 3-8.
Keywords: Boredom -- Fiction; Imagination -- Fiction; Potatoes -- Fiction; Boredom -- Juvenile fiction; Imagination -- Juvenile fiction; Potatoes -- Juvenile fiction; Picture Book